Reimagining Arabic Literature in the Digital Era: Emerging Voices, New Media Trends, and Cross-Cultural Dialogues (Al-Qamar, 2025)
Arabic literature is undergoing a dynamic transformation in the digital era. This article looks at how new technologies and media are changing the way Arabic literature is made, shared, and critiqued in the Arab world. It looks at the growth of digital storytelling platforms and electronic literature, how social media has changed how people express themselves and build communities, and how new Arab voices are using digital channels to get around traditional gatekeepers. The study examines the changing trends in Arabic poetry and prose during a digital transition, such as the rise of flash fiction and spoken word online. It also talks about how technology has made literary criticism more accessible but has also created new problems. Lastly, it talks about multilingualism and cultural conversations in modern Arabic literature, as more and more writers work in different languages and countries, which encourages cross-cultural exchange. The article offers a thorough examination of the present condition and prospective trajectories of Arabic literature in the twenty-first century, utilizing qualitative analysis of recent scholarship, interviews, and case studies. The results show that the literary world is more interactive, open, and connected to the rest of the world than ever before. However, it is still trying to find a balance between tradition and new ideas in the digital age.
Keywords: Arabic literature; digital storytelling; social media; contemporary Arabic writers; Arabic poetry; literary criticism; multilingualism